Near-infrared fluorescence imaging technology guided margin design in oral squamous cell carcinoma: a single-centre retrospective study - Wang, Honghao; Li, Tingyu; Chi, Yifan; Yang, Mingen; Zhao, Li; Hou, Jun (Frontiers in Oncology, 2024)
Objective The margin status of oral squamous cell carcinoma patients is considered to be predictive of recurrence and long-term survival. Therefore, precise intraoperative margin assessment is crucial. This study investigated the feasibility of using near-infrared fluorescence imaging technology to guide margin design in oral squamous cell carcinoma patients. Methods In this retrospective study, indocyanine green solution was intravenously injected preoperatively into patients. Intraoperatively, the surgical area was illuminated using a near-infrared fluorescence imaging system, which caused the lesion to fluoresce in the surgical area. Surgery was performed with the assistance of fluorescence imaging. The fluorescence intensity of the lesion area and surrounding normal tissue was recorded during surgery. Intraoperative margins were sent for rapid pathology, and postoperative margin pathology results were documented. Results Sixteen patients were included in this study (7 males, 9 females), with an average age of 65.65 ± 12.37 years. Preoperative biopsy and postoperative pathology confirmed oral squamous cell carcinoma in all patients. No cancer cells were found in the margin pathology results. The average fluorescence intensity of the lesion area was 214 ± 4.70, and that of the surrounding normal tissue was 104.63 ± 3.14. There was no significant difference in the fluorescence intensity values of the lesion areas among all patients (F=0.38, P>0.05). There was a significant difference in fluorescence intensity between the lesion area and surrounding normal tissue (t=33.76, P<0.05). Conclusion Near-infrared fluorescence imaging technology can aid in real-time imaging differentiation of lesion areas based on differences in fluorescence intensity during surgery. The use of this technology can assist surgeons in assessing the safety margin and reliably guide surgery.